Fatty acid-binding protein 5 (FABP5) modulates limbal epithelial cell homeostasis by regulating the expression of key genes under both normal and inflammatory conditions, in vitro - Maryam Amini; Shao-Lun Hsu; Tanja Stachon; Zhen Li; Ning Chai; Fabian N. Fries; Berthold Seitz; Swarnali Kundu; Shweta Suiwal; Nóra Szentmáry (PLoS ONE, 2026)
Congenital aniridia, a rare disorder caused by PAX6 haploinsufficiency, is characterized by progressive, vision-threatening aniridia-associated keratopathy (AAK) with limbal epithelial dysfunction and chronic inflammation. Downregulation of fatty acid binding protein 5 (FABP5) has been reported in conjunctival cells of congenital aniridia patients and in limbal epithelial cells (LECs) of the PAX6 siRNA knockdown model. We aimed to investigate the effects of FABP5 deficiency on LECs gene expression, without or with inflammatory stimuli. To achieve FABP5 knockdown, human primary LECs were transfected with FABP5 siRNA, using Lipofectamine 2000. Inflammation was induced 48 hours after transfection by incubating cells with 2 µg/mL lipopolysaccharides (LPS) or 1 ng/ml IL-1β. Thereafter, gene and protein levels were examined using qPCR, Western blot and ELISA. Significant downregulation of PAX6 , KRT3 and MMP2 and upregulation of KRT12 mRNA level was observed upon FABP5 knockdown ( p ≤ 0.022). Under inflammatory conditions (IL-1β or LPS treatment), FABP5 knockdown led to reduced PAX6, FOSL2, IL-6, PTGES2, KRT3, MAPK3 and MMP2 ( p ≤ 0.048) and increased VEGFα and CRABP2 mRNA expression levels compared to control LECs ( p ≤ 0.034). Following FABP5 knockdown, reduced PAX6, IL-6 and KRT3 protein levels were confirmed in absence of inflammatory stimuli and in cells treated with IL-1β ( p ≤ 0.034). Our results suggest a novel role of FABP5 protein in AAK progression by controlling expression levels of genes and proteins involved in LEC differentiation. In addition, under inflammatory conditions, FABP5 deficiency affects key transcription factors ( PAX6, FOSL2 ), genes regulating LEC migration, differentiation and cell maintenance ( KRT3, VEGFα, MAPK3, CRABP2 ), and genes involved in inflammation ( IL-6, PTGES2 ).